2007
DOI: 10.1016/j.ejcts.2007.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of severe atherosclerosis of the ascending aorta and aortic arch during cardiac surgery: focus on aortic replacement

Abstract: Despite significant perioperative morbidity, replacement of the severely atherosclerotic aorta is worth consideration to avert expectedly higher death and stroke rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…29,30,60 Hunold et al 64 found severe calcification of the thoracic aorta in 13 of 1812 patients (0.7%) with known or suspected CAD who underwent an EBCT scan. The prevalence of PA was found to be 7.5% in patients evaluated for AS, 7 between 1.2% and 13.6% in patients undergoing valvular or coronary revascularization surgeries, 8,14,[65][66][67][68] and between 5% and 33% in the patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30,60 Hunold et al 64 found severe calcification of the thoracic aorta in 13 of 1812 patients (0.7%) with known or suspected CAD who underwent an EBCT scan. The prevalence of PA was found to be 7.5% in patients evaluated for AS, 7 between 1.2% and 13.6% in patients undergoing valvular or coronary revascularization surgeries, 8,14,[65][66][67][68] and between 5% and 33% in the patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…65 Tricuspid valve and other right-sided procedures can be performed on a beating heart without the need for aortic crossclamping or manipulation. Aortic valve procedures in patients with severe calcification of the ascending aorta mandate the greatest modification of usual techniques.…”
Section: Pa and Cardiac Surgerymentioning
confidence: 99%
“…The presence of severe calcifications in the ascending aorta and aortic arch may alter the course of a scheduled cardiac surgical procedure and is associated with an increased risk of morbidity and mortality [2,8]. A change in the site of cannulation and type of graft upon detection of aortic calcifications after sternotomy may require the use of another myocardial protection technique or intra-aortic balloon occluder [9].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of surgical strategy to decrease manipulation of the unclampable aorta in cardiac surgery, as summarized by Zingone and colleagues. 16 An approach using an endoluminal occluding balloon was demonstrated to be ineffective and associated with a significantly higher risk of in-hospital death and stroke. 7 Deep HCA (<20 C) emerges as a core method to approach the difficult aorta during aortic valve surgery strictly requiring an aortotomy.…”
Section: Discussionmentioning
confidence: 99%